35 The Tissue And Clinical Effects Of Platelet-rich Plasma With Arthroscopic Acromioplasty, A Randomised Clinical Trial. (5th September 2014) - Franklin, Sarah; Murphy, Richard; Rombach, Ines; Wheway, Kim; Watkins, Bridget; Carr, Andrew
Abstract : Introduction: Platelet-rich plasma (PRP) contains a high concentration of autologous platelets and is used as a therapy to aid tendon healing in tendinopathy. No evidence exists of any correlation between tissue changes and clinical symptoms after the application of PRP at the time of surgery for rotator cuff tendinopathy. The aim of this study was to investigate patients undergoing arthroscopic acromioplasty for supraspinatus tendinopathy. It was hypothesised that PRP would cause tissue changes that correlate with patient reported outcomes. Methods: All patients were diagnosed with subacromial impingement syndrome or partial thickness tear. Patients were randomised to receive arthroscopic subacromial decompression (SAD) surgery with or out the application of PRP. Patients and assessors were blinded to which treatment had been allocated. Autologous PRP was prepared using the Magellan ® autologous platelet separator system. Post-operative assessments were carried out at 6 weeks, and 3, 6, and 12 months, and patients were asked to complete the Oxford Shoulder Score (OSS) questionnaire. Core tissue biopsies of the supraspinatus tendon were taken at time of surgery and at the 3-month assessment under local anaesthetic in the outpatient's clinic. Each biopsy was histologically processed and sectioned for H&E, Alcian Blue, and immunohistochemical studies. Bonar scoring was carried out to assess tissue structure and cellular morphology. Antibodies to cell viability, inflammation and pain targets were used and visualised using 3, 3'diaminobenzidine (DAB). Image analysis was performed on the amount of positive DAB staining present, and correlations were performed with the OSS at each time point. Results: Thirty patients received SAD alone and 30 patients received SAD with PRP. There were no significant differences between the patient demographics at baseline. There were no significant differences in the OSS between SAD alone and SAD with PRP at any time point in the study (Figure 1 ). There was no significant difference in the Bonar score between baseline and 3 months despite the significant clinical improvement observed and no difference was observed between the groups (Figure 2 ). Patients receiving PRP had reduced tenocyte cell numbers, reduced blood vessel numbers, and an increase in p53 expression (Figure 3 ). Other biomarkers analysed were not significantly different between the groups. Conclusion: The use of PRP with arthroscopic acromioplasty does not influence clinical outcomes. Of concern we found that PRP use is associated with reduced cell numbers and blood vessels and increased p53 expression, which may be detrimental to long term clinical outcome.